Cellular traffic cops: the interplay between lipids and proteins regulates vesicular formation, trafficking, and signaling in mammalian cells. (December 2015) - Kumar, Amit; Baycin-Hizal, Deniz; Zhang, Yue; Bowen, Michael A; Betenbaugh, Michael J
Graphical abstract: Highlights: Effect of membrane curvature on vesicular trafficking is discussed. Recent studies on lipids' role in controlling translocation of vesicles are discussed. Effects of alteration of membrane lipid profile by proteins are discussed. Studies involving vesicular trafficking events affected by lipid rafts are discussed. Implications of glycerophospholipids in membrane trafficking are discussed. Abstract : Protein secretion and vesicular trafficking in mammalian cells rely on several key lipids including sphingolipids, phospholipids, and neutral lipids crucial to protein processing and other intracellular events. Proteins interact with these lipids to alter the shape of lipid bilayer, thereby playing a pivotal role in cellular sorting. Although some efforts have elucidated the role of these components, extensive studies are needed to further decipher the protein–lipid interactions along with the effect of membrane curvature and rafts in sorting of proteins. The regulatory role of proteins in subcellular localization and metabolism of lipids also needs to be described. Recent studies on the role of lipid–protein interactions in modulating membrane shape, signal transduction, and vesicular trafficking are presented in this review.